INVASIVE TERRESTRIAL PLANT SPECIES IN THE ROMANIAN PROTECTED AREAS. A GEOGRAPHICAL APPROACH - MONICA DUMITRAŞCU; INES GRIGORESCU; GHEORGHE KUSCICSA; MIHAI DOROFTEI; MIHAELA NĂSTASE; CARMEN-SOFIA DRAGOTĂ (Revue Roumaine de Géographie)
The current paper is aiming to present some of the most significant scientific results developed in the framework of FP7 enviroGRIDS project – Building Capacity for a Black Sea Catchment Observation and Assessment supporting Sustainable Development, in terms of assessing the occurrence, development and spread the main Invasive Terrestrial Plant Species (ITPS) in the Romanian protected areas. Taking into consideration the intensification of the human-induced influences in various habitats, the authors undertook an in-depth analysis of selected ITPS (Amorpha fruticosa, Acer Negundo, Ailanthus altissima, Fallopia japonica, Impatiens glandulifera) in relation to the key environmental driving forces in some protected areas considered as case-studies for each biogeographical region in Romania: Maramureş Mountains Natural Park (Alpine region), Mureş Floodplain Natural Park (Pannonic region), Comana Natural Park (Continental region), Măcin Mountains National Park (Steppic region) and Danube Delta Biosphere Reserve (Pontic region). Based on the complex assessment of spatial and statistical data as well as field surveys an ITPS potential distribution model (ITPS-podismod) was also developed. Additionally, some relevant biological indicators (abundance, frequency and ecological significance) in relation to its key environmental driving forces (both natural and humaninduced) have been calculated.